Simvastatin Sensitizes Radioresistant Prostate Cancer Cells by Compromising DNA Double-Strand Break Repair - Chen, Yu-An; Shih, Hua-Wei; Lin, Yi-Chun; Hsu, Hui-Ying; Wu, Tsu-Fang; Tsai, Chen-Han; Wu, Chia-Lin; Wu, Hui-Yu; Hsieh, Jer-Tsong; Tang, Chih-Hsin; Lai, Chih-Ho (Frontiers in Pharmacology, 2018)
Prostate cancer (PCa) is one of the most prevalent male cancers in western world. Radiation therapy (RT) is commonly used to treat PCa patients. However, a certain proportion of patients develop radioresistant PCa cells, which results in metastatic disease. Statins, which inhibit 3-hydroxy-3-methyl glutaryl coenzyme A (HMG-CoA) reductase, are commonly used to treat hypercholesterolemia, exhibiting beneficial effects on cardiovascular diseases and on several types of cancers, including PCa. However, the mechanistic details and crosstalk between statins and RT in PCa cells remain unknown. In this study, radioresistant DOC-2/DAB2 interactive protein (DAB2IP)-deficient PCa cells were used to evaluate whether simvastatin could enhance the effect of ionizing radiation (IR). The crucial molecules that associated with simvastatin elevated radiosensitivity in PCa cells were explored. Our results demonstrated that a combination treatment with simvastatin and IR synergistically induced apoptosis of radioresistant PCa cells. In addition, simvastatin appeared to compromise DNA double-strand breaks (DSB) repair by activating the expressions of histone 2A family member X (γ-H2AX) and phospho-checkpoint kinase 1 (p-CHK1), suggesting an underlying mechanism for this radiosensitization of PCa cells. These findings reveal that simvastatin may be a potent therapeutic agent for co-treatment with radiation to overcome radioresistance in PCa cells.